Wild pigs in North America: history, distribution, ecology, and challenges - Mayer, Jack, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Wild pigs belonging to the species Sus scrofa are not native to the Western Hemisphere. In spite of having had a fairly stable presence in North America during most of the 20th Century, wild pigs on this continent have undergone an explosive increase in both numbers and distribution since 1990. At present these animals are established in 36 US states, four Canadian provinces and a number of Mexican states. Similar to the original introduction from the Old World, this more recent continental increase has been largely man-made. A major part of the reason for the success of this invasive species is that wild pigs are the ultimate survivors, being highly adaptable in many aspects of their biological make-up. Given adequate seasonally-available forage resources and daily access to well-distributed water, shade and escape cover on a year-round basis, these animals are able to live in almost any habitat between the northern boreal forests of Canadian down to the tropical wet jungles of Mexico. Wild pigs have a very high reproductive rate. Finally, with respect to their diet, wild pigs are classified as an opportunistic omnivore, which effectively means that these animals will consume just about anything. Since no viable control mechanisms for pigs currently exist, this situation is only expected to get worse with time. Two future control options currently being investigated include pig-specific toxins and contraceptives. This invasive wild pig crisis has been described as one of the greatest emerging wildlife management challenges facing this continent in the 21st Century.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Sept. 9, 2014.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses